2006
DOI: 10.4028/www.scientific.net/ast.45.2176
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Aspects on the Use of Bayer's Process Bauxite Residue in the Production of Ceramics

Abstract: Bauxite Residue (BR) is the main waste generated during the alumina-producing Bayer process. With the aim to utilize BR in the production of traditional ceramics, the potential impact such a use might have on the leaching behaviour and radioactivity levels of the final products was investigated. Leaching behaviour of Cr, Ni and V on calcined BR was studied according to the maximal availability test, NEN 7341. Firing atmosphere, firing temperature and soaking time were the investigated parameters. Results demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 9 publications
(7 reference statements)
1
4
0
Order By: Relevance
“…Thus, V appears to be the most mobile element, perhaps due to its major association with rather soluble phases. This is in accordance with previous leaching NEN7341 tests concerning BR calcined in inert and reducing atmosphere 11 , as well as in good agreement with recent studies about V in Hungarian BR 1 7 . According to the latter studies, presenting X-ray absorption near-edge structure (XANES) spectroscopic data of vanadium (V K -edge), V in Hungarian BR is pentavalent associated with a Ca-Al-hydroxysilicate phase, corresponding to “hydrogarnet”-type phase.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Thus, V appears to be the most mobile element, perhaps due to its major association with rather soluble phases. This is in accordance with previous leaching NEN7341 tests concerning BR calcined in inert and reducing atmosphere 11 , as well as in good agreement with recent studies about V in Hungarian BR 1 7 . According to the latter studies, presenting X-ray absorption near-edge structure (XANES) spectroscopic data of vanadium (V K -edge), V in Hungarian BR is pentavalent associated with a Ca-Al-hydroxysilicate phase, corresponding to “hydrogarnet”-type phase.…”
Section: Resultssupporting
confidence: 93%
“…As per previous regulations, the plant was allowed to pump the BR directly to the bottom of the sea, at the depth of >100 m. Since 2007, this practice has gradually ceased and through substantial investments (i.e., four filter presses to deliver a semi-dry cake, a new disposal area, a number of research projects for valorization trajectories and more) BR is currently industrially utilized in cement production, with ongoing efforts in the area of ceramics and metallurgy e.g. 11 12 13 . Due to the former disposal practice, millions of metric tones of BR are still remaining on the sea bed of the Antikyra bay e.g.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…2,8,9 and being safe for the humans and the environment. [10][11][12] Previous results 2,9 have demonstrated that the addition of up to 30 wt-%BR in a Greek clay mixture suitable for heavy clay production, results in ceramics with slightly inferior or comparable physical and mechanical properties. For a higher addition, there is a decline in properties.…”
Section: Introductionmentioning
confidence: 99%